Comparison of OvaCyte™ Speciation and PNA staining for the detection of Haemonchus contortus in ovine faecal samples - Elghryani, Nagwa; Lahan, Geetika; Bor Gohain, Jayanta; McOwan, Trish; de Waal, Theo (Frontiers in Veterinary Science, 2025)
BackgroundHaemonchus contortus is one of the most pathogenic and economically important species of gastrointestinal nematodes (GINs) affecting livestock. Recent advancements have led to the development of an artificial intelligence (AI)-powered OvaCyte™ Speciation method, which can quantify the proportion (%) of Haemonchus contortus eggs among strongyle eggs in a faecal sample.MethodsThis study evaluated the diagnostic performance of the OvaCyte™ Speciation method compared to the conventional peanut agglutinin (PNA) fluorescence staining method as a true reference across 110 fresh ovine faecal samples.ResultsOf the total samples, 92 (82.9%) tested positive for Haemonchus contortus. Based on the OvaCyte™ Speciation egg counts, the results showed a marked increase in the mean Haemonchus contortus egg count that corresponded with rising mean strongyle egg counts. A very strong correlation was observed between OvaCyte™ Speciation and peanut agglutinin staining (rₛ = 0.90, p < 0.05). OvaCyte™ Speciation demonstrated a high sensitivity of 100% and a specificity of 89% for the detection of Haemonchus contortus.ConclusionThese findings validate OvaCyte™ Speciation as a reliable alternative to the peanut agglutinin staining method, particularly in field and clinical settings where rapid turnaround and ease of use are critical. Its application could enhance routine herd surveillance and enable evidence-based parasite control in resource-limited or on-farm environments.